Repellency of Citronella Essential Oil in Controlling Pests in Plants - Pupung Purnawan (Eduvest - Journal of Universal Studies, 2024)
This study aims to evaluate the effectiveness of citronella essential oil as a repellency agent in controlling pest attacks on plants. The method used was systematic literature review with data collection through literature studies to collect various types of existing literature to be extracted according to the research title. The findings indicated that citronella essential oil has potential as an environmentally friendly and sustainable pest control method. However, several challenges such as the stability of the oil in the open and the need for periodic reapplication need to be addressed. With an integrated approach that takes into account relevant environmental and technical factors, the use of citronella essential oil can become an integral part of a more effective pest control strategy in agriculture.